Voluntary activation of quadriceps femoris in patients with unilateral anterior cruciate ligament rupture within 6 months of injury: A cross-sectional observational study. (April 2016) - Trees, Amanda; Dixon, John; Howe, Tracey E.
Abstract: Background: Deficits in quadriceps femoris strength and voluntary activation have been well documented in chronic anterior cruciate ligament (ACL) injuries, but less is known about the acute or early phase after injury. Objectives: The aim of this study was to evaluate and compare the levels of quadriceps voluntary activation (VA) and strength in both limbs of participants with unilateral ACL ruptures (complete tears) within 6 months of injury. Design: Cross-sectional observational study. Method: Seventeen participants, 12 male, mean age 30 (17–45) years, performed maximal voluntary isometric contractions with the interpolated twitch technique. Results: Mean (SD) peak VA was significantly lower in the injured limb 76.5 (15.0) % than the uninjured limb 85.9 (6.7) % (p = 0.02). Mean (SD) peak torque in the injured limb was significantly lower 162.7 (74.1) Nm than the uninjured limb 240.5 (81.0) Nm (p < 0.01). Conclusions: This between-limb difference in VA has not previously been observed in patients within 6 months of ACL rupture. Our findings suggest that early rehabilitation programs for adults with ACL rupture should focus on reducing VA deficits to facilitate improvement of the quadriceps femoris muscle strength in the injured limb to comparable values of the uninjured limb. Highlights: Voluntary activation was lower in the injured limb than the uninjured limb. Peak torque was lower in the injured limb than the uninjured limb. Strength and muscle inhibition should be targeted in rehabilitation.